Risalat al-Biruni fi Fihrist Kutub al-Razi: A Comprehensive Bibliography of the Works of Abu Bakr al-Rāzī (D. 313 A.H/925) and al-Birūni (D. 443/1051) - Deuraseh, Nurdeng (Afkar: Jurnal Akidah dan Pemikiran Islam, 2008)
Risalah al-Biruni fi Fihrist Kutub al-Razi is a bibliographical document of two Muslim scholars namely Abu Bakr Muhammad ibn Zakariya al-Razi (m. 313/925) and Abu al-Rayhan Muhammad ibn Ahmad al-Biruni (m. 443/1051). It is a comprehensive bibliography compared with what had been made by Ibn Nadim (m.384/ 995), Ibn Juljul (d. 385/996 C.E), al-Bayhaqi (d. 565 A.H/1170), al-Qifti (d.645/1248), Ibn Abi Usaybi‘ah (d.668 /1266) and Ibn Khallikan (d.681/1283 C.E). The Risalah was written in 427/1036. This article proposes an English translation of the Risalah together with a brief introduction and discussion.